2022
DOI: 10.3390/bs12090336
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Psychological Perspectives and Demographics on Drivers’ Valuation of Road Accidents: A Combination of Confirmatory Factor Analysis and Preference Heterogeneity Model

Abstract: Property damage and loss from road traffic accidents are a major concern in developing countries; thus, studies on accident damage in such countries may include more latent factors. This study aims to examine the effect of psychological perspectives and sociodemographic status on drivers’ willingness-to-pay (WTP) for road accident risk reduction, using confirmatory factor analysis (CFA) and the random parameters multinomial logit model with heterogeneity in means and variances (RPMNLHMV). The CFA results from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Our analysis revealed that all indicators significantly contributed to the SERVQUAL and the HBM factors, with each parameter showing significance at the 0.01 level. While the appropriate AVE and CR values for all factors in this study met the criteria of 0.5 and 0.7, respectively, it is essential to consider the findings from previous literature [50,60]. Their research confirmed that when CR exceeds 0.7, an AVE value higher than 0.4 is still considered acceptable.…”
Section: Observed Indicators and Descriptive Statisticsmentioning
confidence: 55%
“…Our analysis revealed that all indicators significantly contributed to the SERVQUAL and the HBM factors, with each parameter showing significance at the 0.01 level. While the appropriate AVE and CR values for all factors in this study met the criteria of 0.5 and 0.7, respectively, it is essential to consider the findings from previous literature [50,60]. Their research confirmed that when CR exceeds 0.7, an AVE value higher than 0.4 is still considered acceptable.…”
Section: Observed Indicators and Descriptive Statisticsmentioning
confidence: 55%
“…Additionally, EFA results can reduce observed variables by creating new variables in the form of common factors [72]. Therefore, researchers often employ this method when there is no well-established theory regarding the relationships among measurement components [73,74].…”
Section: Analysis Methodologymentioning
confidence: 99%
“…Therefore, there are some issues that require further study, such as the comparison of motorcycle crash severity in urban and rural areas. Determining an appropriate budget for road safety promotion requires considering economic aspects (i.e., where people are willing to pay for safer roads), as highlighted in previous studies [70]. For local roads, this study provides comprehensive recommendations on an overview level, but more precise analysis is required in each area to make more specific policy recommendations [71]…”
Section: Implementationsmentioning
confidence: 98%